Effect of Storage Conditions and Storage Periods on Seed Germination in Eleven Populations of Swertia chirayita: A Critically Endangered Medicinal Herb in Himalaya - Bharat K. Pradhan; Hemant K. Badola (The Scientific World Journal)
Effect of different storage conditions (room temperature, 4°C, and −15°C) and different storage periods over 24 months on seed germination in Swertia chirayita collected from different altitudes in Sikkim Himalaya was determined. Multivariate ANOVA revealed significant (𝑃<0.0001) effect of storage condition and storage period on seed germination and mean germination time. Seed germination percentage significantly (𝑃<0.01) varied between 87.78% (Sc5) and 100% (Sc2) during initial testing. Comparatively, high seed germination, low mean germination time, and low rate of fall in seed germination percentage in seeds stored at 4°C over different storage period were recorded. In addition, above 50% seed germination in majority of the populations even after 24 months of storage suggests 4°C as the most appropriate storage condition for long-term storage of seeds of S. chirayita.